Strategi Social Network Marketing dan Dampaknya Terhadap Consumer Engagement dan Purchase Intention (Studi Kasus Sektor Properti di Indonesia) - Sendi Nopriadi; Lingga Yuliana (Jurnal Ilmiah Global Education, 2026)
This study analyzes the influence of Social Network Marketing (SNM) on Consumer Engagement and Consumer Purchase Intention in the real estate sector in Indonesia, which is currently experiencing accelerated digital transformation and changes in consumer behavior. Using a quantitative approach with 157 respondents who have purchased property in the Greater Jakarta area, the data was processed using Smart Partial Least Squares. The results of the study indicate that the first hypothesis indicates that Social Network Marketing has a positive and significant influence on Consumer Engagement. The second hypothesis indicates that Social Network Marketing has a significant influence on Consumer Purchase Intention. Meanwhile, the third hypothesis indicates that Social Network Marketing has a significant influence on Consumer Purchase Intention. Managerial implications emphasize that property companies in Indonesia need to optimize Social Network Marketing as a primary strategy to build engagement and drive purchase intention. Marketing managers need to focus on creating informative, engaging, and interactive content, as well as ensuring fast and personalized two-way communication to strengthen consumer trust. In addition, the integration of digital technologies such as virtual tours, live streaming open houses, chatbots, and social media analytics can increase marketing effectiveness in directing the consumer journey from awareness to purchase.